2021
DOI: 10.4018/ijisss.2021100105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Facilitating Conditions and Usage Experience on Mobile Payment

Abstract: The following research attempts to investigate the determinants influencing consumers' intention to adopt mobile payment (MP). The research model was adapted based on three constructs from the unified theory of acceptance and use of technology (UTAUT), including performance expectancy, effort expectancy, and facilitating conditions in the research model. In addition, usage experience was also added to the model to test for moderating effect. An online survey conducted through Taiwanese chat rooms resulted in 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…Previous studies on mobile payment consumers indicated that facilitating conditions significantly predict individuals' intention to use mobile payment (Gupta & Arora, 2020;Purwanto & Loisa, 2020). These findings are consistent with recent research conducted among the Taiwanese, which indicated that facilitating conditions were among the major factors influencing consumers' intention to use mobile payment (Tsai, 2021).…”
Section: Literature Reviewsupporting
confidence: 92%
“…Previous studies on mobile payment consumers indicated that facilitating conditions significantly predict individuals' intention to use mobile payment (Gupta & Arora, 2020;Purwanto & Loisa, 2020). These findings are consistent with recent research conducted among the Taiwanese, which indicated that facilitating conditions were among the major factors influencing consumers' intention to use mobile payment (Tsai, 2021).…”
Section: Literature Reviewsupporting
confidence: 92%